Simple Views on Condensed Matter - Pierre-Gilles de Gennes (World Scientific, 1992)
A selection of papers by Pierre-Gilles de Gennes - 1991 Nobel Prize winner in Physics - which have had a long-lasting impact on our understanding of condensed matter. Important ideas on polymers, liquid crystals and interfaces are described. The author has added some afterthoughts to the main papers (explaining their successes or weaknesses), and some current views on each special problem